Remission of long-term hepatic and renal disease induced by HCV after direct-acting antivirals therapy - Arruda,Raissa M (2021)
Abstract In addition to liver disease, the hepatitis C virus (HCV) has been associated with autoimmune phenomena, such as mixed cryoglobulin and glomerulonephritis (GN). Until recently, both chronic hepatitis and HCV extra-hepatic manifestations were treated with peg-interferon plus ribavirin, however these drugs presented low efficacy and induced severe side effects. Nowadays, the HCV chronic hepatitis has been treated with direct acting antivirals (DAA), but studies on the DAA therapy for HCV-associated glomerulonephritis are scarce. Here, we describe two cases of HCV-associated glomerulonephritis that were treated with DAAs. In these two cases, previously experienced to peg-interferon plus ribavirin, the sofosbuvir plus simeprevir therapy was effective, without significant side effects, and interrupted the evolution of at least 20 years of both hepatic and renal diseases. These cases join the seven previously described cases that were treated with this DAAs association.